Changing paradigms in anticancer drug development: inhibiting angiogenesis in colorectal cancer - Kerr, David (Henry Stewart Talks, 2009)
Targeted therapy for cancer, Angiogenesis is involved throughout tumour formation, growth and metastasis, VEGF: molecular characteristics, VEGF and other signals promote the angiogenic switch in tumours, Tumour vasculature is abnormal, VEGF produces immature tortuous vessels dependent on VEGF for survival, Other features make VEGF an attractive target for anticancer therapy, RhuMAb VEGF (bevacizumab/Avastin(R)), Significant reduction in microvasculature, Anti-VEGF antibody improves drug delivery, Avastin: an anti-VEGF agent for cancer therapy, Use of Avastin with oxaliplatin-based therapy, Addition of Avastin to oxaliplatin-based chemotherapy improved best confirmed response, Study schema and organization
Archived at 2021/02/25